2023
DOI: 10.1002/adhm.202301338
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Cardiac Tissue for Advanced Heart‐On‐A‐Chip Platforms

Xinyi Chen,
Sitian Liu,
Mingying Han
et al.

Abstract: Cardiovascular disease is a major cause of mortality worldwide, and current preclinical models including traditional animal models and 2D cell culture models have limitations in replicating human native heart physiology and response to drugs. Heart‐on‐a‐chip (HoC) technology offers a promising solution by combining the advantages of cardiac tissue engineering and microfluidics to create in vitro 3D cardiac models, which can mimic key aspects of human microphysiological systems and provide controllable microenv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 156 publications
(293 reference statements)
0
8
0
Order By: Relevance
“…Zhao et al reported real-time monitoring of cellular environments using surface-engineered cells with aptamers that bind to platelet-derived growth factor (PDGF) and contain a pair of fluorescent dyes [ 142 ]. Although this approach necessitates an additional fluorescence microscope for monitoring cellular environments, efforts to integrate these systems into sensor platforms have resulted in the development of various types of biosensors based on engineered cells and tissues [ 143 , 144 , 145 ].…”
Section: Biosensor Systems For Cell Monitoringmentioning
confidence: 99%
“…Zhao et al reported real-time monitoring of cellular environments using surface-engineered cells with aptamers that bind to platelet-derived growth factor (PDGF) and contain a pair of fluorescent dyes [ 142 ]. Although this approach necessitates an additional fluorescence microscope for monitoring cellular environments, efforts to integrate these systems into sensor platforms have resulted in the development of various types of biosensors based on engineered cells and tissues [ 143 , 144 , 145 ].…”
Section: Biosensor Systems For Cell Monitoringmentioning
confidence: 99%
“…These sensors rely on electrochemical or photochemical reactions, which are difficult to replicate in animal models. 44 Within the modular OOC integration platform, the OOC platform was housed in a custom benchtop incubator that could maintain optimal temperature and carbon dioxide levels. It was equipped with biophysical sensors to detect pH, oxygen levels, and temperature, as well as electrochemical immunomonitoring for protein markers such as glutathione S-transferase, creatine kinase MB (CK-MB), and organoid morphology.…”
Section: ■ Electrochemical Sensorsmentioning
confidence: 99%
“…However, the diffusion process for providing oxygen and nutrients to the cardiac microtissue is limited. To improve the clinical feasibility of the tissue model, thicker tissue needs to be constructed, which would involve producing a capillary network within the tissue to deliver nutrients to the cells …”
Section: Vascularized Organ-on-a-chipmentioning
confidence: 99%
See 2 more Smart Citations